Pengaruh Pengetahuan Perpajakan Terhadap Minat Mengikuti Brevet Pajak - Dewi Kusuma Wardani; Fira Yunia (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to test whether knowledge of taxationaffect the interest of accounting students to take tax brevet. This study uses quantitative descriptions and primary data by obtaining data from respondents using a questionnaire. The number of samples in this study were 84 respondents. The sample was distributed to 84 respondents of accounting students, Faculty of Economics, University Sarjanawiyata Tamansiswa Yogyakarta. Sampling in this study used the snowball sampling method to obtain data according to the sample. This study found that taxation knowledge had a positive effect on student interest in taking tax brevet